TiN coating effect on the elastoplastic behaviour of Ti film for electron beam exit window - Knyazeva A. G. Anna Georgievna; Kushch V. I. Vladimir Ivanovich; Remnev (Remnyov) G. E. Gennady Efimovich; Ezhov V. V. Vitali Vladimirovich; Smolyanskiy (Smolyansky, Smolyanskii) E. A. Egor Aleksandrovich (2017, 2017)
Title screen